Fecal impaction, perianal trauma and rectal foreign bodies - Ayten, Refik; Başbu?, Murat; Çetinkaya, Ziya (My University, 2009)
Fecal impaction is a common gastrointestinal problem and a potential source of major morbidity. Prompt identification and treatment minimizes the risks. Treatment includes proximal or distal washout or manuel extraction. After treatment, possible causes should be sought and prevention therapy should be instituted. Traumatic injury to the anus and sphincters is uncommon. Most of these injuries are iatrogenic, with obstetrical injuries being the most common. Sphincter injury should be identified. If the patient is stable and there is minimal tissue loss, primary repair may be considered. The presence of foreign bodies in the rectum is an uncommon clinical problem. The most frequent form of introduction is through the anal passage (generally for sextual purposes), followed by oral ingestion and migration from neighbouring organs. Although many foreign bodies can be extracted safely in the emergency department some patients require hospitalization and surgery.
Gai?ta tikaci, peri?anal yaralanmalar ve rektal yabanci ci?si?mler
Keywords: anus injury; clinical feature; emergency treatment; feces impaction; foreign body; hospitalization; human; iatrogenic disease; pathophysiology; review